2018
DOI: 10.1002/ajh.25056
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetyl‐L‐cysteine improves bone marrow endothelial progenitor cells in prolonged isolated thrombocytopenia patients post allogeneic hematopoietic stem cell transplantation

Abstract: Prolonged isolated thrombocytopenia (PT) is a serious complication following allogeneic hematopoietic stem cell transplantation (allo-HSCT). According to murine studies, endothelial progenitor cells (EPCs) play a crucial role in the regulation of hematopoiesis and thrombopoiesis in the bone marrow (BM) microenvironment. We previously showed that the reduced frequency of BM EPCs was an independent risk factor for the occurrence of PT following allo-HSCT. However, the functional role of BM EPCs and methods to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 49 publications
2
65
0
Order By: Relevance
“…The definitions of PGF and GGF were consistent with those of previous studies [9][10][11][12][13][14]24,26,27]. PGF was defined as hypoplastic or aplastic BM with 2 or 3 of the following: neutrophil count .5 £ 10 9 /L, platelet count 20 £ 10 9 /L, and/or hemoglobin concentration 70 g/L for at least 3 consecutive days after day +28 post-HSCT or in accordance with the platelet, RBC ), pre-HSCT cycles of chemotherapy ( §1 cycle), disease status at HSCT, and BM microenvironment evaluated time after allo-HSCT ( §5 days).…”
Section: Definitions Of Pgf and Ggfsupporting
confidence: 89%
See 2 more Smart Citations
“…The definitions of PGF and GGF were consistent with those of previous studies [9][10][11][12][13][14]24,26,27]. PGF was defined as hypoplastic or aplastic BM with 2 or 3 of the following: neutrophil count .5 £ 10 9 /L, platelet count 20 £ 10 9 /L, and/or hemoglobin concentration 70 g/L for at least 3 consecutive days after day +28 post-HSCT or in accordance with the platelet, RBC ), pre-HSCT cycles of chemotherapy ( §1 cycle), disease status at HSCT, and BM microenvironment evaluated time after allo-HSCT ( §5 days).…”
Section: Definitions Of Pgf and Ggfsupporting
confidence: 89%
“…Poor graft function (PGF), characterized by pancytopenia, is a severe complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT) [1][2][3]. However, the exact pathogenesis of PGF remains unclear, and effective treatment options for PGF are limited [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BM trephine biopsies (BMBs) were obtained from the posterior superior iliac spine of the patients with or without aGVHD and healthy donors. As previously described (Duan et al , ; Kong et al , ,b), the immunofluorescence staining of EPCs in the BMBs were performed with the mouse anti‐human CD34 (Becton Dickinson) and rabbit anti‐human CD133 (Abcam, Cambridge, MA, USA) antibodies. The goat anti‐rabbit 555 and donkey anti‐mouse 488 (Invitrogen, Carlsbad, CA, USA) antibodies were added at RT for 1 h. 4′,6‐Diamidino‐2‐phenylindole (DAPI) was applied to stain the nuclei, and the prepared slides were analysed under a Leica TCS SP8 microscope (Leica Microsystems, Wetzlar, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, EPCs improved the quality and quantity of transplanted haematopoietic stem cells (HSCs) in mice (Qiao et al , ). More recently, we reported that impaired BM EPCs contribute to the occurrence of poor graft function (PGF) and prolonged isolated thrombocytopenia (PT) after allo‐HSCT in humans (Kong et al , , , ; Shi et al , ). We further found that disruption of the BM EPCs may hamper the differentiation progress from HSCs to megakaryocytes, resulting in the occurrence of corticosteroid‐resistant immune thrombocytopenia (ITP), indicating that immune‐mediated platelet destruction is not the sole pathogenic mechanism of corticosteroid‐resistant ITP (Kong et al , ).…”
mentioning
confidence: 99%